Referrals from community optometrists to the hospital eye service in England. (22nd December 2020) - Evans, Bruce J W; Edgar, David F; Jessa, Zahra; Yammouni, Robert; Campbell, Peter; Soteri, Kiki; Hobby, Angharad; Khatoon, Abeeda; Beg, Amaad; Harsum, Steven; Aggarwal, Rajesh; Shah, Rakhee
Abstract: Purpose: In the UK, most referrals to the hospital eye service (HES) originate from community optometrists (CO). This audit investigates the quality of referrals, replies, and communication between CO and the HES. Methods: Optometric referrals and replies were extracted from three practices in England. If no reply letter was found, the records were searched at each local HES unit, and additional replies or records copied. De‐identified referrals, replies and records were audited by a panel against established standards to evaluate whether the referrals were necessary, accurate and directed to the appropriate professional. The referral rate (RR) and referral reply rate (RRR) were calculated. Results: A total of 459 de‐identified referrals were extracted. The RR ranged from 3.6%–8.7%. The proportion of referred patients who were seen in the HES unit was 63%–76%. From the CO perspective, the proportion of referrals for which they received replies ranged from 26%–49%. Adjusting the number of referrals for cases when it would be reasonable to expect an HES reply, RRR becomes 38%–62%. Patients received a copy of the reply in 3%–21% of cases. Referrals were made to the appropriate service in over 95% of cases, were judged necessary in 93%–97% and were accurate in 81%–98% of cases. The referral reply addressed the reason for the referral in 93%–97% and was meaningful in 94%–99% of cases. The most common conditions referred were glaucoma, cataract, anterior segment lesions, and neurological/ocular motor anomalies. The CO/HES dyad (pairing) in the area with the lowest average household income had the highest RR. Conclusions: In contrast with the Royal College of Ophthalmologists/College of Optometrists joint statement on sharing patient information, CO referrals often do not elicit a reply to the referring CO. Replies from the HES to COs are important for patient care, benefitting patients and clinicians, and minimising unnecessary HES appointments.